2021
DOI: 10.3389/fcell.2021.731062
|View full text |Cite
|
Sign up to set email alerts
|

The Advancing Roles of Exosomes in Breast Cancer

Abstract: Breast cancer (BC) develops from breast tissue and is the most common aggressive malignant tumor in women worldwide. Although advanced treatment strategies have been applied and reduced current mortality rates, BC control remains unsatisfactory. It is essential to elucidate the underlying molecular mechanisms to assist clinical options. Exosomes are a type of extracellular vesicles and mediate cellular communications by delivering various biomolecules (oncogenes, oncomiRs, proteins, and even pharmacological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 133 publications
(144 reference statements)
0
18
0
3
Order By: Relevance
“…Therefore, drugs targeting this class of drug-resistant oncomiRs can resensitize the BC cells to chemotherapies. Recently, MSC-released exosomes, containing specific miRNA sequences, are being utilized for the targeted killing of chemoresistant bCSCs ( 201 , 223 ).…”
Section: Bcsc-related Mirna Signature Modulating Stemness and Drug Re...mentioning
confidence: 99%
“…Therefore, drugs targeting this class of drug-resistant oncomiRs can resensitize the BC cells to chemotherapies. Recently, MSC-released exosomes, containing specific miRNA sequences, are being utilized for the targeted killing of chemoresistant bCSCs ( 201 , 223 ).…”
Section: Bcsc-related Mirna Signature Modulating Stemness and Drug Re...mentioning
confidence: 99%
“…It was observed that exosomes are biodistributed via body fluids to transport drugs or biomolecules to the cancer cells within the vicinity or dwelling remotely, which offers an advantage in recognizing potential pathological situations. The exosomes follow various uptake mechanisms namely direct membrane fusion, or endocytosis [ 100 ].…”
Section: Lipid-based Nanoparticles: a Versatile Drug Delivery Systemmentioning
confidence: 99%
“…The intercellular communicator role of exosomes has made them a promising research entity for their potential metastasis-promoting and metastasis-inhibiting abilities while affecting the cells of the tumor microenvironment. Markedly, the non-coding RNA cargo of exosomes is believed to enable the promotion or inhibition of metastasis via epigenetic regulation [ 37 ] Literature evidence revealed that exosomal miRNAs could be transferred from tumor-derived exosomes into normal cells, promoting metastasis. MiR-500a-5p transferred from CAFs-derived exosomes was shown to enhance breast cancer metastasis by binding to ubiquitin-specific peptidase 28 (USP28) [ 22 ].…”
Section: Oncogenic and Tumor Suppressor Roles Of Exosomal Non-coding ...mentioning
confidence: 99%